Culinary Reorientation As A Cultural Asset In The Development Of Sustainable Tourism Based On Community Economy - Mahmudi Mahmudi (Program Studi Pendidikan IPS, 2023)
This research aims to analyze culinary reorientation as a cultural asset in the development of sustainable tourism based on the community economy. The data collection technique involves documentation from relevant journals and literature sources, such as Google Scholar. The data analysis is carried out using critical literature evaluation. The results showed that culinary can play a significant role in sustainable tourism development, particularly in empowering the economy of local communities. In this context, strengthening and promoting culinary heritage as a cultural asset can enhance the attractiveness of tourism destinations, create job opportunities, and improve the welfare of local communities. By integrating community economic practices, culinary-based tourism can serve as a sustainable source of income while preserving traditional culture in the long term.